Fibronectin Binding Is Required for Acquisition of Mesenchymal/Endothelial Differentiation Potential in Human Circulating Monocytes. (1st November 2012) - Seta, Noriyuki; Okazaki, Yuka; Izumi, Keisuke; Miyazaki, Hiroshi; Kato, Takashi; Kuwana, Masataka
Abstract : We previously reported monocyte-derived multipotential cells (MOMCs), which include progenitors capable of differentiating into a variety of mesenchymal cells and endothelial cells. In vitro generation of MOMCs from circulating CD14 + monocytes requires their binding to extracellular matrix (ECM) protein and exposure to soluble factor(s) derived from circulating CD14 - cells. Here, we investigated the molecular factors involved in MOMC generation by examining the binding of monocytes to ECM proteins. We found that MOMCs were obtained on the fibronectin, but not on type I collagen, laminin, or poly-L-lysine. MOMC generation was followed by changes in the expression profiles of transcription factors and was completely inhibited by either anti- α 5 integrin antibody or a synthetic peptide that competed with the RGD domain for the β 1 -integrin binding site. These results indicate that acquisition of the multidifferentiation potential by circulating monocytes depends on their binding to the RGD domain of fibronectin via cell-surface α 5 β 1 integrin.